Past, present and future of university hospitals. Issue 3 (3rd May 2020) - Raus, Kasper; Mortier, Eric; Eeckloo, Kristof
ABSTRACT: Objectives : Health care systems worldwide are changing and taking new forms. The old, more hierarchically oriented, model with individual institutional and bilateral interactions between primary, secondary, tertiary and quaternary care is being replaced by an integrated and dynamic network model. We aim to look at what role university hospitals will play in this future organization of health care. Method : In this paper, we look at the relevant literature on the history of academic medicine and university hospitals. Subsequently, we look at the challenges university hospitals are facing according to contemporary literature on the topic. Results : Our current model of academic medicine with its university hospitals finds its origin in the institutionalization of the academic mission in the late 18 th century. Currently, the sustainability of the model is under immense pressure. University hospitals are facing economic challenges, teaching challenges and research challenges. However, there is reason to believe that they can continue to play a role of importance in tomorrow's medicine. The organization of health care is undergoing two important changes. The first is the evolution towards a more dynamic and integrated network model. University hospitals can become an important hub within this network. The second change is an evolution towards evidence based medicine and translational research. Conclusion : Due to their unique tripartite mission, we argue that university hospitals can continue to play an important and critical role in promoting evidence-based medicine and speedy translation of new evidence.